2017
DOI: 10.1016/j.jpainsymman.2017.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Burnout After Patient Death: Challenges for Direct Care Workers

Abstract: Context Direct care workers in long-term care can develop close relationships with their patients and subsequently experience significant grief after patient death (Boerner et al., 2015). Consequences of this experience for employment outcomes have received little attention. Objectives To (1) investigate staff, institutional, patient, and grief factors as predictors of burnout dimensions among direct care workers who had experienced recent patient death, (2) determine which specific aspects of these factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 32 publications
(45 reference statements)
2
45
1
Order By: Relevance
“…In this article, we confirm and build upon the existing research demonstrating that client death can have negative effects on the lives of home care workers (Boerner et al, 2015; Boerner et al, 2017; Delp et al, 2010) and that several types of support are needed to reduce these effects (Boerner et al, 2016; Gleason, Boerner, & Barooah, 2016). In examining aides’ grief strategies, we found some that were similar to those of nurses working with end-of-life clients (e.g., seeking emotional connection and attempting to set boundaries) and others that were largely distinct—specifically, the general lack of employer support in the postloss period and the need to rely primarily on one’s own personal strength to cope with grief.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In this article, we confirm and build upon the existing research demonstrating that client death can have negative effects on the lives of home care workers (Boerner et al, 2015; Boerner et al, 2017; Delp et al, 2010) and that several types of support are needed to reduce these effects (Boerner et al, 2016; Gleason, Boerner, & Barooah, 2016). In examining aides’ grief strategies, we found some that were similar to those of nurses working with end-of-life clients (e.g., seeking emotional connection and attempting to set boundaries) and others that were largely distinct—specifically, the general lack of employer support in the postloss period and the need to rely primarily on one’s own personal strength to cope with grief.…”
Section: Discussionsupporting
confidence: 61%
“…The authors also learned that agency policies rarely allow aides to stay in contact with clients’ families after a death and that few aides felt they could seek support from their supervisors (Boerner, Gleason, & Barooah, 2016; van Riesenbeck, Boerner, Barooah, & Burack, 2015). The grief and lack of support following a client’s death are thus critical problems that likely reduce job satisfaction, increase burnout and turnover, and compromise home care workers’ health and the care they provide (Boerner, Gleason, & Jopp, 2017).…”
mentioning
confidence: 99%
“…24 Having supportive supervisors and team leaders who exhibited the qualities of transformational leadership like genuineness and compassion also led to less burnout. 25,26 We found that the exposure to stress in the form of Personal and professional struggles was often necessary to build resilience. Cavanaugh et al 27 described these as challenge stressors as opportunities for growth and development.…”
Section: Main Findingsmentioning
confidence: 99%
“…What evidence exists suggests there is a need to prepare staff via better education about bereavement (Österlind et al, 2011) and a need to have bereavement support mechanisms in place (Carton & Hupcey, 2014;Boerner et al, 2015). Some evidence suggests that grief over residents' deaths play an overlooked role in direct care worker burnout (Boerner et al, 2017). Key recommendations for support include peer debriefing and support (Chen et al, 2019;Vis et al, 2016).…”
Section: Review 8: Supporting Staff Following Deaths In Care Homesmentioning
confidence: 99%